2013
DOI: 10.1055/s-0033-1340283
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Copper-Powder-Catalyzed Synthesis of Pyrimidinones from β-Bromo α,β-Unsaturated Carboxylic Acids and Amidines

Abstract: β-Bromo α,β-unsaturated carboxylic acids were coupled and cyclized with amidine hydrochlorides by microwave irradiation in the presence of catalytic amounts of copper powder and a base to give the corresponding pyrimidinones in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Evaporation of the solvent gave a crude mixture that was purified using TLC (ethyl acetate–hexane). Except for known 3a and 3b , all new products prepared by the above procedure were characterized spectroscopically as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaporation of the solvent gave a crude mixture that was purified using TLC (ethyl acetate–hexane). Except for known 3a and 3b , all new products prepared by the above procedure were characterized spectroscopically as described below.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that β‐bromo‐α,β‐unsaturated amides are coupled and cyclized with formamide in the presence of CuI and a base without an additional ligand to give pyrimidinones . Such a similar coupling and cyclization leading to pyrimidinones is also exemplified by the reaction of β‐bromo‐α,β‐unsaturated carboxylic acids and amidine hydrochlorides in the presence of copper powder under microwave irradiation conditions . It is also reported that quinazolin‐4(3 H )‐ones can be synthesized by CuI‐catalyzed coupling of 2‐iodobenzamides with amidine acetates followed by condensation cyclization .…”
Section: Introductionmentioning
confidence: 97%
“…As a result, after further tuning the reaction temperature and time (entries 9 and 10), the best result in terms of both product yield and complete conversion of 1a was accomplished using the standard set of reaction conditions shown in Table 1, entry 11. 15 When used with tripotassium phosphate and N,N-dimethylformamide, copper(I) salts such as copper(I) chloride, bromide, iodide, or acetate showed slightly lower catalytic activity than copper powder (entries [11][12][13][14][15].…”
Section: Syn Thesismentioning
confidence: 99%
“…10 We recently have shown that β-bromo-α,β-unsaturated carboxylic acids undergo coupling and cyclization with amidine hydrochlorides in the presence of copper powder under microwave irradiation to give pyrimidinones. 11 The present work was disclosed during the course of the application of the copper powder/microwave irradiation system in the synthesis of pyrimidinones to the reaction of β-bromo-α,β-unsaturated carboxylic acids with 1,3-diketones. This report describes an efficient and rapid protocol for the synthesis of 2Hpyran-2-ones by copper-powder-catalyzed coupling and cyclization of β-bromo-α,β-unsaturated carboxylic acids with 1,3-diketones under microwave irradiation (Scheme 1).…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] β-Bromo-α,β-unsaturated aldehydes and their derivatives are readily prepared from α-methylene group-containing ketones by bromination under Vilsmeier-Haack conditions [20,21] and subsequent transformation, and the products can serve as valuable building blocks for the construction of various cyclic compounds. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Among such carbonlative cyclization reactions, we recently have shown that β-bromo-α,β-unsaturated carboxylic acids can be carbonylatively cyclized with 2,2-dimethylhydrazine under carbon monoxide pressure in the presence of a palladium catalyst to give 1-(dimethylamino)-1H-pyrrole-2,5-diones. [39] The present work arose during the course of the application of this protocol to the reaction with arylhydrazines.…”
Section: Introductionmentioning
confidence: 99%